Computer Modelling as an Aid to Forest and Woodland Restoration - Majer, Jonathan; Dunn, A.; Orsini, J. (Society of American Foresters, 2014)
Reclamation of terrestrial ecosystems tends to be focussed on two main land uses, mining and degraded agricultural or forested lands. Modelling has great potential to assist in both situations. The aim of many restoration programs is to restore biodiversity and a self-sustaining, fully functional ecosystem, which is intimately linked with the return of the plants, the vertebrates and, particularly, the invertebrate fauna, whose presence plays a pivotal role in most ecosystem functions and processes. A thorough understanding of these plant-fauna associations is essential if restoration is to succeed. It could also equip us with the knowledge to decide how minimalistic our information needs can be when modelling progress with restoration, for instance: by quantifying certain biophysical parameters; these plus certain vegetation indices; or by both plus a range of faunal attributes. As well as streamlining the restoration monitoring process, this could lead to the enhancement of the conservation value of the restoration, and a clear understanding of the ecological links between flora and fauna would also help develop bioindicators as components of completion criteria schedules. Using Western Australian bauxite mining in the Jarrah (Eucalyptus marginata) forest as a case study, this paper reviews rehabilitation prescriptions and trends in development of plant assemblages, invertebrate colonization and litter decomposition, and applies a systems dynamic modelling approach model to test assumptions regarding the evolution of plant-fauna assemblages in time and assess whether it is feasible to predict temporal changes in the rehabilitation of this ecosystem. Secondly, in relation to efforts to purchase and rehabilitate land to reconnect remnant woodland vegetation close to the south coast of Western Australia, network analysis and multi-level simulations are applied in order to decide the best locations to acquire land and to restore it in order to optimise connectivity.